2014
DOI: 10.1002/app.40395
|View full text |Cite
|
Sign up to set email alerts
|

Bis[4‐(4‐maleimidephen‐oxy)phenyl]propane/N,N‐4,4′‐bismaleimidodiphenylmethyene blend modified with diallyl bisphenol A

Abstract: In this article, 2,2′‐bis[4‐(4‐maleimidephen‐oxy)phenyl)]propane (BMPP) resin and N,N‐4,4′‐bismaleimidodiphenylmethyene (BDM) resin blends were modified by diallyl bisphenol A (DABPA). The effects of the mole concentration of BMPP on mechanical properties, fracture toughness, and heat resistance of the modified resins were investigated. Scanning electron microscopy was used to study the microstructure of the fractured modified resins. The introduction of BMPP resin improves the fracture toughness and impact st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The second exothermic peak is owing to the Diels–Adler reaction and the anionic imide oligomerization at elevated temperatures. 7…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The second exothermic peak is owing to the Diels–Adler reaction and the anionic imide oligomerization at elevated temperatures. 7…”
Section: Resultsmentioning
confidence: 99%
“…6 Among the various allyl compounds, 2,2-diallylbisphenol A (DABPA) is known to be one of the ideal modifiers for BMI toughening modification. 7 Furthermore, the BMI resin modified by DABPA possesses high heat resistance and excellent mechanical properties, which greatly improves the processing performance. 8,9 N , N ′-(4,4′-diphenylmethane) bismaleimide (BDM), as a commonly used resin modified by DABPA, occupies an extremely important position in the BMI family.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase of temperature ranges for low melt viscosity was benefit to forming processes that need wide processing window. 22,23 Microstructure analysis of MWCNTs/CE resin system…”
Section: Effect Of Mwcnts On the Curing Behavior And Temperature Of Cmentioning
confidence: 99%
“…Mixing this monomer into the conventional BDM/DABA system leads to the formation of a material with promising properties [36]. Firstly, rheological characterisation showed that the uncured blend is able to maintain a low viscosity over a wide temperature range (100 -180 °C), meaning that the material has a broad processing window but with no change in curing temperature.…”
Section: Improving Toughness In Cured Bmismentioning
confidence: 99%